Incidence and Challenges in Management of Blood Stream Infections in Hemodialysis - Khatun, Nargis; Khan, Aaliya; Arfat, Mohd.; Siddiqui, Sharmin; Khan, Sohrab A. (International Journal of Membrane Science and Technology, 2023)
Bloodstream infections pose a significant threat to patients undergoing hemodialysis, leading to hospitalizations, increased morbidity, and mortality. The Centers for Disease Control and Prevention (CDC) has prioritized the prevention of bloodstream infections in hemodialysis through their Making Dialysis Safer initiative.Most bloodstream infections linked to vascular access primarily occur in patients undergoing dialysis using central vein catheters. The Centers for Disease Control and Prevention (CDC) advocates core interventions as the best practices for catheter care in hemodialysis, demonstrating their effectiveness in reducing catheter-associated bloodstream infections. However, bloodstream infections linked to hemodialysis catheters persist at undesirable levels, it is likely due to failures in maintaining rigorous aseptic techniques or other factors beyond the scope of the CDC’s core interventions. There is a urgent need for innovation of preventive measures. This review focuses on the current therapies, recent developments and also addresses potential drawbacks and adverse effects associated with thealternatives. This review also highlights the challenges and future perspectives which might prove to be beneficial in reducing infection rates in hemodialysis patients.